Semiaquatic mammals might be intermediate hosts to spread avian influenza viruses from avian to human - Zhao, Ping (Sci Rep, 2019)
Avian influenza A viruses (AIVs) can occasionally transmit to mammals and lead to the development of human pandemic. A species of mammal is considered as a mixing vessel in the process of host adaptation. So far, pigs are considered as a plausible intermediate host for the generation of human pandemic strains, and are labelled ‘mixing vessels’. In this study, through the analysis of two professional databases, the Influenza Virus Resource of NCBI and the Global Initiative on Sharing Avian Influenza Data (GISAID), we found that the species of mink (Neovison vison) can be infected by more subtypes of influenza A viruses with considerably higher α-diversity related indices. It suggested that the semiaquatic mammals (riverside mammals), rather than pigs, might be the intermediate host to spread AIVs and serve as a potential mixing vessel for the interspecies transmission among birds, mammals and human. In epidemic areas, minks, possibly some other semiaquatic mammals as well, could be an important sentinel species for influenza surveillance and early warning.